Molecular Changes in the Cardiac RyR2 With Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) - Dulhunty, Angela F. (Frontiers in Physiology, 2022)
The cardiac ryanodine receptor Ca2+ release channel (RyR2) is inserted into the membrane of intracellular sarcoplasmic reticulum (SR) myocyte Ca2+ stores, where it releases the Ca2+ essential for contraction. Mutations in proteins involved in Ca2+ signaling can lead to catecholaminergic polymorphic ventricular tachycardia (CPVT). The most common cellular phenotype in CPVT is higher than normal cytoplasmic Ca2+ concentrations during diastole due to Ca2+ leak from the SR through mutant RyR2. Arrhythmias are triggered when the surface membrane sodium calcium exchanger (NCX) lowers cytoplasmic Ca2+ by importing 3 Na+ ions to extrude one Ca2+ ion. The Na+ influx leads to delayed after depolarizations (DADs) which trigger arrhythmia when reaching action potential threshold. Present therapies use drugs developed for different purposes that serendipitously reduce RyR2 Ca2+ leak, but can adversely effect systolic Ca2+ release and other target processes. Ideal drugs would specifically reverse the effect of individual mutations, without altering normal channel function. Such drugs will depend on the location of the mutation in the 4967-residue monomer and the effect of the mutation on local structure, and downstream effects on structures along the conformational pathway to the pore. Such atomic resolution information is only now becoming available. This perspective provides a summary of known or predicted structural changes associated with a handful of CPVT mutations. Known molecular changes associated with RyR opening are discussed, as well one study where minute molecular changes with a particular mutation have been tracked from the N-terminal mutation site to gating residues in the channel pore.